Methodology for teaching French phraseological units and methods of their translation into Russian and Uzbek languages (1-4 undergraduate courses) - Alimova Gulnoza (Zien Journals, 2022)
An important role in the process of teaching French, in particular French phraseological units, is played by the methodology of teaching French phraseological units and methods of their translation into Russian and Uzbek. To date, insufficient knowledge of phraseological units of a foreign language is noted among university teachers and subsequently among students. The topic of this dissertation meets the stated conditions and therefore seems relevant. The object of the study is the process of teaching the techniques of translating French phraseological units of Uzbek-Russian bilinguals in a language university. The purpose of this study is to develop a methodological basis for French phraseological units as the basis of a series of exercises for teaching Uzbek-Russian bilinguals the techniques of their translation russian phraseology In order to achieve the goal, It is necessary to solve the following tasks: to consider the linguistic nature of phraseological units in general, and the phraseology of the French, Uzbek and Russian languages, in particular, to outline the nomenclature of phraseological units of the French language graded by linguistic complexity; to analyze the essence of translation techniques and their psychological basis and to identify difficulties in translating French phraseological units for Uzbek-Russian bilinguals; by means of an intelligence experiment to concretize linguistic and psychological difficulties of understanding and translating phraseological units of the French language in the form of methodological ranking; to create a methodology for teaching French phraseological units and on its basis to develop appropriate exercises; to experiment. To solve the tasks, the following research methods are used: comparative analysis of phraseological units of the Uzbek, Russian and French languages, linguodidactic method, experimental method, phraseological identification method, linguocultural description method, control method, empirical method. Russian Russian phraseological units in the comparative analysis with Uzbek and Russian languages, an attempt is made to create methodological foundations of phraseological units of the French language, designed to teach the techniques of translation of Uzbek-Russian bilinguals, the construction of a linguadidactic model of mastering the phraseology of the French language with Uzbek and Russian phraseological units in a practical course of teaching three languages. The practical value consists in a specific (scientifically based and experimentally proven) method of teaching Uzbek-Russian
Keywords: Phraseological; semantics; experiment; emotional awareness